Knowledge and attitudes toward the use of anabolic–androgenic steroids among physical education university students: a cross-sectional study from Palestine - Suhaib Hattab; Bashar Saleh; Laith Qasarweh; Mahmoud Draidi; Sa’ed H. Zyoud (Scientific Reports, 2024)
Abstract The use of androgenic–anabolic steroids (AASs) has increased in recent years, especially among athletes, due to their effect on body shape and performance. These agents could have serious side effects on this highly susceptible population, which tends to use these substances frequently to promote muscle growth and physical performance. Therefore, this study aimed to evaluate the knowledge and attitudes toward the use of anabolic androgenic steroids among physical education university students in Palestine. A cross-sectional study of physical education students from November 2020 to January 2021 was conducted using an electronic questionnaire. The main outcome was to measure the level of knowledge and use of the AAS. A total of 380 students were included. The mean age of the students was 21 years (SD = 4.2), and the study participants were distributed almost equally according to sex. Approximately a quarter of the students were smokers. Eighty percent (80%) of the study participants were from the West Bank, while the remaining 20% were from Jerusalem and 48 territories. Furthermore, most of the students lived with their families; half lived in cities, approximately 152 (40%) lived in villages, and only 29 (8%) lived in camps. The average level of knowledge of the AAS was 2.95 out of 8 (37/100), with a median of three. Furthermore, only 36 (10%) of the participants had satisfactory knowledge, scoring 80% or more. Regarding the use of AAS, 11 (2.9%) participants, all males, confirmed that they were currently using AAS. Additionally, approximately 28 (7%) had previously used them, while 30 (8%) planned to try them in the future. Overall, 221 (58%) patients were confirmed to use vitamins and minerals. Our study showed that most of the participants had a substantial lack of information on the potential side effects of AAS, while the level of use was comparable with that of other populations.